2009
DOI: 10.1177/147323000903700221
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Degeneration of Nigra-striatum Dopaminergic Neurons Induced by 1-Methyl-4-phenyl-1,2,3, 6-tetrahydropyridine in Mice

Abstract: As one of the main pathological changes of Parkinson's disease (PD), axonal degeneration was thought to be a passive process that is secondary to the apoptosis of dopaminergic neurons and, therefore, it has been overlooked for some time. Recent research, however, has indicated that axonal injury is the first location of damage in dopaminergic neurons in PD, and that the degree of injury in axonal degeneration is higher than in neural death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 15 publications
(36 reference statements)
2
14
0
Order By: Relevance
“…In the present study, an increase in the t-SOD activity observed in the SN and CS of the EF1 group was able to protect these regions from membrane LP measured as TBARS levels. The absence of FJC labeling in neuronal cell bodies of both brain regions reinforces these results, considering the efficacy of this reagent in detecting signals of neurodegeneration induced by conditions of OS, such as ischemia (Yang et al, 2011), glutamate excitotoxicity (Ehara and Ueda, 2009) or dopaminergic lesions induced by 6-OHDA (Ehara and Ueda, 2009) or MPTP (Bian et al, 2007; Li et al, 2009). …”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…In the present study, an increase in the t-SOD activity observed in the SN and CS of the EF1 group was able to protect these regions from membrane LP measured as TBARS levels. The absence of FJC labeling in neuronal cell bodies of both brain regions reinforces these results, considering the efficacy of this reagent in detecting signals of neurodegeneration induced by conditions of OS, such as ischemia (Yang et al, 2011), glutamate excitotoxicity (Ehara and Ueda, 2009) or dopaminergic lesions induced by 6-OHDA (Ehara and Ueda, 2009) or MPTP (Bian et al, 2007; Li et al, 2009). …”
Section: Discussionmentioning
confidence: 64%
“…It has been shown that this protocol specifically labels damaged neurons and not glial cells in the SN and CS (Bian et al, 2007; Ehara and Ueda, 2009) when these regions are submitted to certain types of insult, especially under conditions that induce OS (Ehara and Ueda, 2009; Li et al, 2009; Yang et al, 2011). …”
Section: Methodsmentioning
confidence: 99%
“…Early aggregation might result in early dysfunction at the presynaptic terminal, causing defects in neurotransmission long before cell death. In multiple models of PD, both toxin-induced (Herkenham et al, 1991; Orimo et al, 2008; Li et al, 2009a; Cartelli et al, 2010; Arnold et al, 2011; Kim-Han et al, 2011; Mijatovic et al, 2011) and genetic (Li et al, 2009b; Decressac et al, 2012) axon degeneration is observed prior to cell death, and in a higher percentage of cells. This has raised the question of whether PD represents a ‘dying back’ of dopaminergic neurons (Hornykiewicz, 1998), with synapse loss initiating a retrograde degenerative process that leads to cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the MPTP model is an excellent tool for the study of axonal degeneration. Already within the first days after MPTP application, the number of tyrosine hydroxylase-immunoreactive fibres in the median forebrain bundle significantly decreases, whereas the dopaminergic neuron demise follows later (Li et al , 2009). In an elaborate study analysing synaptosomal preparations of MPTP-treated mice, chronically administered MPTP readily decreased the expression of the dopamine transporter at a time when cell bodies still remained intact (Muroyama et al , 2011).…”
Section: Introductionmentioning
confidence: 99%